2015
DOI: 10.1037/cns0000039
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mindfulness on emotion dysregulation and psychophysiological reactivity under emotional provocation.

Abstract: While support continues to mount for the effectiveness of mindfulness training in improving psychological functioning, researchers are only beginning to examine its mechanisms of action. The present study employed multimodal assessment of the experience and regulation of emotion to examine the effects of a brief mindfulness intervention. Seventy undergraduate students at a small southern state university were randomly assigned to listen to a 15-min recording of either a mindfulness intervention or neutral reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 88 publications
(279 reference statements)
1
14
0
Order By: Relevance
“…to relate to higher vmHRV, however these authors did not report the relation between vmHRV and the other FFMQ subscale scores nor the total FFMQ score. Krygier et al, 2013;May et al, 2016;Nijjar et al, 2014;Shearer, Hunt, Chowdhury, & Nicol, 2016;Takahashi et al, 2005;Tang et al, 2009;Watford & Stafford, 2015), however one study (Nyklicek, Mommersteeg, Van Beugen, Ramakers, & Van Boxtel, 2013) did not find an effect of mindfulness training on vmHRV. As mindfulness training has been shown to increase also selfcompassion levels (Kuyken et al, 2010), however, these findings cannot necessarily be interpreted as to signify that mindfulness in itself relates to higher vmHRV.…”
Section: The Relation Between Mindfulness and Vmhrvmentioning
confidence: 99%
See 1 more Smart Citation
“…to relate to higher vmHRV, however these authors did not report the relation between vmHRV and the other FFMQ subscale scores nor the total FFMQ score. Krygier et al, 2013;May et al, 2016;Nijjar et al, 2014;Shearer, Hunt, Chowdhury, & Nicol, 2016;Takahashi et al, 2005;Tang et al, 2009;Watford & Stafford, 2015), however one study (Nyklicek, Mommersteeg, Van Beugen, Ramakers, & Van Boxtel, 2013) did not find an effect of mindfulness training on vmHRV. As mindfulness training has been shown to increase also selfcompassion levels (Kuyken et al, 2010), however, these findings cannot necessarily be interpreted as to signify that mindfulness in itself relates to higher vmHRV.…”
Section: The Relation Between Mindfulness and Vmhrvmentioning
confidence: 99%
“…The applied vmHRV measure was HF. HF is the most commonly used in previous research examining associations between self-compassion, mindfulness and vmHRV (Azam et al, 2015;Delgado-Pastor et al, 2013;Krygier et al, 2013;May et al, 2016;Nijjar et al, 2014;Nyklicek et al, 2013;Takahashi et al, 2005;Tang et al, 2009;Watford & Stafford, 2015) and is considered a valid measure of vmHRV…”
Section: Resting Vmhrvmentioning
confidence: 99%
“…However, we are still unsure of how these constructs are specifically related to one another. Future research may wish to continue utilizing experimental design and behavioral indicators to successfully compliment the current self-report measures of mindfulness to further examine the relationships between constructs (see Arch and Craske 2006;Keng et al 2017;Watford and Stafford 2015). A recent meta-analysis of mindfulness and emotion regulation showcases methodological developments in this research field, and confirms the relationship between these constructs through experimental manipulation (Leyland et al 2018).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Likewise, Kadziolka et al (2016) found the FFMQ-subscales of "Observe" and "Acting with Awareness" to relate to a higher vmHRV after a stress induction task. Interestingly, in contrast to measuring dispositional mindfulness, a more consistent relationship is found between mindfulness training and increased levels of vmHRV (e.g., Takahashi et al, 2005;Ditto et al, 2006;Tang et al, 2009;Joo et al, 2010;Delgado-Pastor et al, 2013;Krygier et al, 2013;Nijjar et al, 2014;Azam et al, 2015;Watford and Stafford, 2015;May et al, 2016;Shearer et al, 2016), although one study did not find such an effect of mindfulness training on level of vmHRV (Nyklicek et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…It showed that only self-compassion predicted better abilities in mood drop and spontaneous mood-recovery when including both mindfulness (measured with the MAAS) and self-compassion (measured with the SCS) as predictors in the same regression model. Dispositional mindfulness (e.g., Delgado-Pastor et al, 2013;Krygier et al, 2013;Nijjar et al, 2014;Watford and Stafford, 2015;May et al, 2016;Shearer et al, 2016) and dispositional selfcompassion (Rockliff et al, 2008;Kok et al, 2013;Arch et al, 2014;Matos et al, 2017;Petrocchi et al, 2017) are further also linked to psychophysiological flexibility as measured with higher vagally mediated heart rate variability (vmHRV). However, as far as we know, no study has yet attempted to disentangle the effect of dispositional self-compassion from dispositional mindfulness on vmHRV.…”
Section: Introductionmentioning
confidence: 99%